2003
DOI: 10.1021/jf0212542
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Polyphenol Oxidase from Garland Chrysanthemum (Chrysanthemum coronariumL.)

Abstract: Polyphenol oxidase (PPO) of garland chrysanthemum (Chrysanthemum coronarium L.) was purified approximately 32-fold with a recovery rate of 16% by ammonium sulfate fractionation, ion exchange chromatography, hydrophobic chromatography, and gel filtration. The purified enzyme appeared as a single band on PAGE and SDS-PAGE. The molecular weight of the enzyme was estimated to be about 47000 and 45000 by gel filtration and SDS-PAGE, respectively. The purified enzyme quickly oxidized chlorogenic acid and (-)-epicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Although it has been reported that C. coronarium had an anti-bacterial activity and an anti-oxidant activity by the components such as polyphenolic compounds [16][17][18]27], there were few research papers described about the immuno-potentiating effects. In addition, we demonstrated here that the extract of C. coronarium activated Type-1 immunity via TLR-signaling cascades of DC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been reported that C. coronarium had an anti-bacterial activity and an anti-oxidant activity by the components such as polyphenolic compounds [16][17][18]27], there were few research papers described about the immuno-potentiating effects. In addition, we demonstrated here that the extract of C. coronarium activated Type-1 immunity via TLR-signaling cascades of DC.…”
Section: Discussionmentioning
confidence: 99%
“…The edible part of C. coronarium, such as the leaf and the stem, contains abundant β-carotene, iron, calcium, and dietary fiber [15]. In addition to these nutrients, it has been reported that C. coronarium has several compounds responsible for the antioxidant activity [16,17] and anti-inflammatory effect [18]. However, it has not International Immunopharmacology 11 (2011) …”
Section: Introductionmentioning
confidence: 99%
“…Table 1 and 2 showed substrate specificity of crude PPO from various Indonesia's and Japan's cruciferae vegetables. Generally, PPO oxidized o-diphenols, as listed in Table 3, garland chrysanthemum (Nkya et al, 2003) strongly oxidized chlorogenic acid and epicatechin; Japanese butterbur ) and apple (Murata et al, 1992) strongly oxidized chlorogenic acid; banana pulp and peel (Yang et al, 2000;2001) (Jia et al, 2011) strongly oxidized catechol. However, substrate specificity of crude PPO from various Indonesia's and Japan's cruciferae vegetables (Table 1 and 2) showed different activity, all the cruciferae vegetables PPOs tested did not show activity toward o-diphenol.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidation of phenolic compounds by polyphenol oxidase (PPO) in the damaged tissue induced undesirable browning, resulting decrease the nutritional value of vegetables. Generally, PPO oxidized o-diphenols, such as found in Japanese butterbur ) and edible burdock ) strongly oxidized chlorogenic acid; edible yam strongly oxidized dopamine; broccoli florest (Gawlik-Dziki et al, 2007), mango (Wang et al, 2007) and mamey (Palma-Orozco et al, 2011) strongly oxidized catechol; garland chrysanthemum (Nkya et al, 2003) strongly oxidized catechol and epicatechin . On the other hand, the purified enzyme of soybean (Toiguchi et al, 1989) and one of the purified enzymes of edible burdock (Murao et al, 1993) not oxidized o-diphenols, but oxidized pyrogallol (1,2,3-trihydroxybenzene) and phloroglucinol (1,3,5-trihydroxybenzene).…”
Section: Introductionmentioning
confidence: 99%
“…In both the times of exposure, the enzyme was inactivated when treated at 80°C. Nkya et al [31] studied the stability of PPO from garland chrysanthemum and observed that the enzyme maintains its activity when treated at 50°C for 10 and 30 min, while the treatment at 80°C for 10 min induced the loss of 90% of the activity and complete inactivation of the enzyme was obtained when the treatment was carried out during 30 min. Extracts of PPO of iceberg lettuce incubated at 1 h at 50, 65, and 75°C showed a percentage of activity remaining of 72, 31, and 0%, respectively.…”
Section: Resultsmentioning
confidence: 99%